Studi Fenomenologi tentang Pengalaman Pustakawan dalam Memberikan Layanan Referensi di Era Digital - Jalinur (Perpustakaan Universitas Riau, 2026)
This study aims to explore librarians’ experiences in providing reference services in the digital era. Using a phenomenological approach, the study seeks to understand the meaning and essence of librarians’ experiences in interacting with users and in addressing the challenges and opportunities arising from the development of digital technology. Through in-depth interviews with experienced librarians in delivering reference services, this research reveals their perceptions, emotions, and reflections on the changes occurring within the library environment. The findings highlight challenges such as the need to develop new skills, adapt to rapidly evolving digital resources, and respond to shifting user preferences. Nevertheless, the digital era also presents promising opportunities for library professionals to enhance their services through the use of technology and broader access to information resources. This study provides valuable insights into how librarians interpret their roles in the context of digital transformation and how they negotiate their professional identity amid ongoing changes in the library world.